Anatomical relations of root formation in strawberry - Papp, J.; Gracza, P.; Simon, G. (International Journal of Horticultural Science, 2004)
Anatomical relations of root formation are traced throughout the life cycle of the strawberry plant from the germinating seed up to the runners of the adult plant. Histological picture of the root changes a lot during the development of the plant. First the radicle of the germ grows to a main root, which makes branches into side roots and later adventitious roots are formed on the growing rootstock or rhizome. The anatomy of the different types of roots is also conspicuously different. First tiny branches appear relatively early after germination on the seedling’s radicle, but soon the hypocotyl of the seedling thickens and develops side roots, which are already somewhat stronger. During this interval, the first true leaves are formed. The 4th or 5th of them being already tripartite, and the initiation of new roots extends into the epicotylar region of the shoot. The second years growth starts with the development of reproductive structures, inflorescences and runners starting from the axils of the new leaves. Near the tips of the runners below the small bunch of leaves, new root primordia are initiated. The tiny radicle of the germ develops a cortical region of 5-6 cell layers. Cells of the central cylinder are even smaller than the cortical parenchyma and include 3-4 xylem and 3-4 phloem elements as representatives of the conductive tissue. Roots originating from the shoot region are much more developed; their cortical zone contains 17-20 cell layers, whereas the central cylinder is about half as large. In the next year, new roots are formed at the base of the older leaves. These roots differ hardly from those of the last season in size and volume, however, they are recognised by colour and their position on the rhizome. The roots of the last year are dark, greyish-black, and grow on the lower third length of the rhizome, on the contrary, the new ones, on the upper region, are light brown. Roots starting from the shoot or rhizome are, independently from their age or sequence, mainly rather similar in size and diameter, thus being members of a homogenous root (homorhizous) system, i.e. without a main root. Plants developed and attained the reproductive phase develop in the axils of the leaves runners being plagiotropic, i.e. growing horizontally on the surface of the soil. The runners elongate intensely, become 150-200 mm, where some long internodes bear a bunch of small leaves and root primordia on short internodes and a growing tip. Runners do not stop growing, generally, further sections of 15-25 cm length are developed according to the same pattern, with small leaves on the tip. The growing tip of the runners is obliquely oriented, and small, conical root primordia are ready to start growing as soon as they touch the soil. The roots penetrate the soil, quickly, and pull, by contraction, the axis of the runner downwards, vertically, developing a new rhizome. The short internodes elongate a little and start developing adventitious roots. At the end of the growing season, the plantlets arisen on the rooted nods of runners are already similar to the original plants with homogenous root system. On the side of the adventitious roots, new branches (side-roots) are formed. The root-branches are thinner but their capillary zone is more developed being more active in uptake of water and nutrients. The usual thickening ensues later.